Strategy of the Human Resources Department in Recruiting Quality Employees at Quest Prime Pemuda Hotel in Semarang. - Tiga Anugerah Ramadhani; Syaiful Ade Septemuryantoro (International Forum of Researchers and Lecturers, 2023)
The Human Resources Department has the responsibility to oversee and manage human resources and everything related to the strategy of recruiting quality employees and the period of time when the Human Resources Department is looking for new candidate replacements. The importance of the ability to recruit quality employees for the Human Resources Department is one of the factors in improving professional human resources, and recruitment problems can be resolved well, thus reducing existing issues. This study aims to determine the strategy of recruiting quality employees at the Quest Prime Hotel and to overcome obstacles in the employee recruitment process at the Quest Prime Hotel. This research is a qualitative study that takes place at the Quest Prime Pemuda Hotel in Semarang. The subject of this study is the Human Resources Manager. The methods used in this study are Observation, Interview, and Documentation, thus obtaining accurate data. The form of recruitment process implemented by the Human Resources Department is by analyzing the required positions, screening the workforce, conducting interviews and selections, and making decisions, so as to obtain new employees with quality standards.